Increasing tropical cyclone residence time along the Chinese coastline driven by track rotation - Linjiang Li; Johnny C. L. Chan; Guihua Wang; Yunxia Zheng (npj Climate and Atmospheric Science)
Abstract Coastal regions are highly vulnerable to tropical cyclones (TCs), with the severity of damage often closely linked to the duration of storms over these areas. Here we show a significant increase in TC residence time along the Chinese coast, with an average rise of approximately 2.5 h per decade since the 1980s. While the overall translation speed of TCs does not show any significant trend, their travel distances within coastal zones have increased markedly, rising by about 32.9 km per decade. This trend is particularly pronounced in the southern coastal region (south of 26°N), where TC tracks exhibit a counterclockwise rotation to become more parallel to the coastline since the 1980s. A concomitant counterclockwise rotation in the steering flow near this region is also observed, which is likely driven by the northward shift of the western Pacific subtropical high. These changes in TC trajectories have also led to prolonged durations of heavy rainfall in the coastal regions.